2015
DOI: 10.1038/srep11388
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin scattering in multi-core optical fibers for sensing applications

Abstract: We measure the Brillouin gain spectra in two cores (the central core and one of the outer cores) of a ~3-m-long, silica-based, 7-core multi-core fiber (MCF) with incident light of 1.55 μm wavelength, and investigate the Brillouin frequency shift (BFS) and its dependence on strain and temperature. The BFSs of both the cores are ~10.92 GHz, and the strain- and temperature-dependence coefficients of the BFS in the central core are 484.8 MHz/% and 1.08 MHz/°C, respectively, whereas those in the outer core are 516.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 46 publications
(120 reference statements)
0
29
0
Order By: Relevance
“…Another alternative solution to separate the effects of strain and temperature in Brillouin distributed sensors is to use two cores simultaneously, whose strain/temperature sensitivities are different [54][55][56][57][58] . This is achievable by using a heterogeneous MCF, whose cores are made from different preforms.…”
Section: Distributed Curvature and Shape Sensing Using Brillouin Scatmentioning
confidence: 99%
“…Another alternative solution to separate the effects of strain and temperature in Brillouin distributed sensors is to use two cores simultaneously, whose strain/temperature sensitivities are different [54][55][56][57][58] . This is achievable by using a heterogeneous MCF, whose cores are made from different preforms.…”
Section: Distributed Curvature and Shape Sensing Using Brillouin Scatmentioning
confidence: 99%
“…In this case, the two cores have non-overlapping values of ν B and have differing thermal and strain coefficients. Mizuno et al [124] described the use of multi-(7-) core fiber for the distributed Brillouin sensing application, but only characterized two of the cores for said application. They found that the thermal and strain coefficients differed by <10% in the first and second cores, but with one parameter being larger and the other being smaller in the first core.…”
Section: Fiber Configurationsmentioning
confidence: 99%
“…All these reported transducers are however fiber-based point (discrete) sensors, which do not exploit the distributed sensing capabilities offered by the optical fiber. MCFs have been only recently investigated for distributed strain and temperature sensing based on stimulated Brillouin scattering [16]. Reference 16 actually reports that temperature and strain sensitivities of Brillouin scattering in any core of a MCF are comparable and essentially identical to standard single-core optical fibers.…”
Section: Introductionmentioning
confidence: 99%